The TRUSTS Work System Resilience Framework: A Foundation for Resilience-Aware Development and Transition. (September 2022) - Neville, Kelly J.; Pires, Bianica; Madhavan, Poornima; Booth, Matthew; Rosfjord, Kris; Patterson, Emily S.
Despite decades of effort to improve information technology (IT) transition, the success rate remains low with each failure representing substantial losses of time, money, and resources. When technologies do transition, they often are ignored and worked around. Worse, they may disrupt work or interfere with work-system responses to challenges. We posit that a systems-centered approach to transition grounded in complex-systems science and resilience engineering can significantly improve technology adoption rates. To serve as the foundation for this approach, we developed a framework that specifies resilience characteristics of high-consequence work systems. The framework, called the Transform with Resilience during Upgrades to Socio-Technical Systems (TRUSTS) Framework, is the basis for IT development tools and guidance that enable resilience-aware development and transition. The tools and guidance will help development teams design and evaluate technologies that contribute to work system performance during escalated and nonroutine demands and conditions, i.e., to work system resilience.